Peran Wawancara Narasumber Kompeten Pada Acara Talkshow Dalam Menciptakan Kesadaran Masyarakat Indonesia Sebagai Warga Negara yang Baik - Maula, Putri Ni’matul; Ginting, Gladies Agina; Syafi’i, Azhari Dwi; Friyadhi, Naufal Farros; Maniari, Elsa; Yohana, Maria; Hasnakusumah, Raisha Tiara; Marsanthy, Talitha Aqiella; Mahardika, Agus; Verrell Y.S, Jevon; Asri, Muh Rozi; S, Subakdi (Media Hukum Indonesia (MHI), 2025)
The role of interviews in talk shows as a medium for shaping public awareness of civic values is an effective way to convey values from various aspects and experiences of the interviewees with the talk show host through casual conversation, but still within the scope of the discussion. The study employed a qualitative method with a content analysis approach on various talk show episodes covering social, legal, educational, and cultural themes. Data collection was conducted using the observation-recording method from a total of 33 talk show episodes across 11 national television programs and digital platforms. The research results indicate that talk shows have strong educational potential in conveying moral messages, national values, and encouraging active community participation in national and state life. The civic values that emerge in the programs include: integrity, justice, equality, inclusivity, environmental awareness, legal compliance, and social participation. The inclusive representation of sources reflects the diversity and involvement of various elements of society in building civic values. The findings and recommendations discussed in this article emphasize the importance of monitoring and developing the quality of talk show content as an effective non-formal civic education tool.